2022
DOI: 10.1038/s41467-022-34460-w
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic characterization of MiT family translocation renal cell carcinoma

Abstract: Microphthalmia transcription factor (MiT) family translocation renal cell carcinoma (tRCC) is a rare type of kidney cancer, which is not well characterized. Here we show the comprehensive proteogenomic analysis of tRCC tumors and normal adjacent tissues to elucidate the molecular landscape of this disease. Our study reveals that defective DNA repair plays an important role in tRCC carcinogenesis and progression. Metabolic processes are markedly dysregulated at both the mRNA and protein levels. Proteomic and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 104 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…One possibility is that the development of TRCC in Asian populations might be related to exposure to aristolochic acid, a type of carcinogen from traditional Chinese herbs, as recently demonstrated in a large study analyzing the mutational signature of Asian patients with TRCC. 20 Another possibility is related to differences in the biological underpinnings of RCC in African versus European populations, as was recently demonstrated. 7 We acknowledge several limitations in our study.…”
Section: Discussionmentioning
confidence: 97%
“…One possibility is that the development of TRCC in Asian populations might be related to exposure to aristolochic acid, a type of carcinogen from traditional Chinese herbs, as recently demonstrated in a large study analyzing the mutational signature of Asian patients with TRCC. 20 Another possibility is related to differences in the biological underpinnings of RCC in African versus European populations, as was recently demonstrated. 7 We acknowledge several limitations in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a high-throughput sequencing-based study of 79 cases of TFE3 rRCCs indicated that the TCA cycle and respiratory chain were down-regulated in TFE3 rRCC compared to adjacent tissues, which is compliant with Warburg Effect [ 39 ]. However, it is demonstrated in our previous research that mitochondrial respiration is significantly enhanced in TFE3 rRCC than that in ccRCC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MITF family translocation RCC (t-RCC) is a rare subtype that accounts for 1% to 4% of RCC cases in adults and around 50% in children. 6 It is usually characterized by gene fusions involving transcription factor binding to IGHM enhancer 3 ( TFE3 ) and transcription factor EB ( TFEB ), 2 members of the MITF family of transcription factors. 7 The most common chromosomal translocations associated with tRCC are Xp11, which involves the oncogenic activation of the TFE3 transcription factor, and, less frequently, 6;11 (p21;q12), involving TFEB .…”
Section: Discussionmentioning
confidence: 99%